2021
DOI: 10.12911/22998993/137359
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Oxyphinic Elements in Sewage Sludge Fractions Based on Manganese and Nickel

Abstract: Owing to the chemical composition of sewage sludge (SS), it may be used as an alternative to fertilizers; however, before land application, it must be assessed in terms of its contents of heavy metals considering their potential mobility in the soil. The aim of this study was focused on evaluating the potential mobility of oxyphinic elements -Mn and Ni in SS. The samples were collected from 4 different wastewaters treatment plants located in the Wielkopolska province at the same time points in 3 consecutive ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…This study revealed a mean concentration of 7.82 ± 2.43 mg/kg for manganese, with concentrations ranging from 5.02 to 9.39 mg/kg. It is worth noting that there seems to be no maximum amount of Mn in biosolids because it represents a valuable micronutrient for plants, birds, and animals, and poses a low hazard to the environment [26] , [41] . Our findings indicated a lower mean concentration of Mn, compared to sewage sludge in Poland which documented concentrations between 65.43 and 224.19 mg/kg [26] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study revealed a mean concentration of 7.82 ± 2.43 mg/kg for manganese, with concentrations ranging from 5.02 to 9.39 mg/kg. It is worth noting that there seems to be no maximum amount of Mn in biosolids because it represents a valuable micronutrient for plants, birds, and animals, and poses a low hazard to the environment [26] , [41] . Our findings indicated a lower mean concentration of Mn, compared to sewage sludge in Poland which documented concentrations between 65.43 and 224.19 mg/kg [26] .…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that there seems to be no maximum amount of Mn in biosolids because it represents a valuable micronutrient for plants, birds, and animals, and poses a low hazard to the environment [26] , [41] . Our findings indicated a lower mean concentration of Mn, compared to sewage sludge in Poland which documented concentrations between 65.43 and 224.19 mg/kg [26] . Concentrations of Mn in PTS at Barekese WTP may be attributed to the utilization of brown calcitic lime in drinking water treatment, which contains higher amounts of Mn than white lime owing to its low manganese content [42] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, this is essential information, and the total contents of heavy metals in SS can provide important but general knowledge. However, toxicity, mobility, bioavailability, and geochemical processes of metals in the environment depend strongly on their geochemical fraction [11,[21][22][23]. Generally, metals can be found in various forms: water-soluble, exchangeable, carbonate-bound, bound to Mn, Fe oxides and hydroxides, bound to organic matter, or they appear in the residual fraction.…”
Section: Introductionmentioning
confidence: 99%